The Effect of Transmission Ratio and the Number of Teeth on Involute Spur Gear Geometrical Characteristics, Load Sharing Ratio, and Contact Stress - Hmoad, Nassear Rahseid; Abdulkareem, Aveen Ahmed (Engineering, Technology & Applied Science Research, 2025)
Among the numerous gear advantages, the speed ratio plays an important role in transmitting mechanical power and control tooth geometry, which is in turn affect the bending and contact tooth strength. The aim of this work is to study the geometry of involute teeth for a different teeth number and speed ratio regarding the second moment of mass numerically, in addition to the investigating the induced contact stress analytically based on the Hertz contact model, and numerically using the Finite Element Method (FEM). The bending stress for the mating teeth has been investigated numerically for their loaded sides. The parameters studied are the pressure angles, speed ratio and gear teeth number, as well as the contact ratio and load sharing. The results show that in general increasing the speed ratio decreases the contact stress for different pressure angles. Higher pressure angles have lower induced bending and contact stresses at a contact ratio lower than 9. However, a larger contact ratio increases the 14.5o teeth strength, where the shared load reduced by about 33%.